Analisis Beban Kerja Untuk Menentukan Jumlah Karyawan Pabrik Roti Sri Rejeki Menggunakan Metode FTE - Rahmi Rismayani Deri; Desi Cahyati; Nurul Hidayati (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
Sri Rejeki bakery is one of the home industries in Bandung Regency which has been established since 1986 until now and produces various types of bread with one shift of 7 employees, and above average working hours of 11 hours. It is known that the actual conditions in the company are not optimal because the workload is not evenly distributed at each work station, this causes many complaints from employees that lead to high workloads. Based on these problems, if not resolved, these problems can affect the employees physically and psychologically and can reduce factory productivity. Therefore, this research was conducted by analyzing the workload of employees to determine the number of employees so that work can be more effective and efficient. Workload analysis problem solving in this study uses the Full time Equivalent method. From the results of the full time equivalent calculation analysis, the workload values for the dough, molding, baking and packaging work stations were 125%, 133%, 122%, and 151%, respectively. A total of 2 employees in the Normal category (FTE 1-1.28) and 5 workers in the overload category (FTE> 1.28). So the company needs to add employees, 1 employee in the molding work unit and 1 employee in the packaging unit. The addition of 2 employees will make the average workload normal value between the FTE index 1-1.28.